THE ROLE OF SMALL AND MEDIUM MICRO ENTERPRISES (MSMEs) IN ECONOMIC DEVELOPMENT IN CIREBON DISTRICT - Oxy Hendro Prabowo (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
SMEs are in a position strategic for speed up change structural To use increase level life many people, and is a place where producers and consumers operate together . If MSMEs become entity production and competition main in economy nationally , the Indonesian economy will have solid foundation . _ Importance the role of SMEs, goals from study this is for identify the role of MSMEs and the problems they face perpetrator MSME business in development economy . Type study this is studies case with use approach qualitative . Respondent study this are SMEs in Cirebon Regency . Source of data obtained from primary and secondary data through technique data collection with use interviews , observations and documents . Data analysis techniques work with research data with method listen , select data, analyze data, analyze data, and draw conclusion . Finding study this is the role of SMEs is expected could expand opportunity work , give significant contribution _ to growth economy , balance growth income , as well as increase power competitiveness and resilience economy national . difficulty and cost ingredient raw , distribution operation hampered , capitalization and production obstructed . Recommendation from study this is effort micro and small expected could adapt with technology moment this for increase power competitive product and optimize potency institution finance that can Becomes alternative source funding for rural SMEs.